Cultural mapping a guide to understanding place, community and continuity - Pillai, Janet (Strategic Information and Research Development Centre, 2020)
"Cultural mapping is an approach to recording and revealing an integrated picture of cultural character, significance and workings of a place. The second edition of Janet Pillai's book contains everything you need to know about this process, and how to plan and begin your own projects. 'This guide on Cultural Mapping provides an invaluable resource for everyone interested in having a deeper understanding of the unique character and identity of a historic place and its community. It provides the user with a clear methodology for unraveling the complex and significant elements that make up any human settlement. Step-by-step procedures outline the processes, tools and techniques for collecting and assessing the cultural assets and resources of a given community. Several illustrated case applications of cultural mapping from Malaysia and Hong Kong have been included to help demonstrate the application of cultural mapping in tourism, conservation, revitalisation and education projects. This is a remarkable resource which advocates that cultural mapping should be the basis for all urban planning studies to ensure that culturally sensitive and appropriate decisions are made in the planning, management and development of small and large historic sites and in place-making exercises. A must use for policy makers, planners, cultural advocates and leaders."